2019
DOI: 10.1002/adom.201901767
|View full text |Cite
|
Sign up to set email alerts
|

IR Artificial Compound Eye

Abstract: In this work, a 3D IR artificial compound eye (ACE) optical component is fabricated using thermoplastic IR polymer material. The femtosecond laser‐assisted wet etching and the 3D nano‐imprinting techniques are proposed for fabricating this thin shell multi‐aperture component. The prepared component is close‐packed with over 1000 high‐quality micro‐facet‐lenslets (ommatidia) on the semispherical thin shell dome with base radius of 2.7 mm and sag height of 2.1 mm, enabling enlarged field of view to 148°. The omm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 47 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…Benefit from the extreme nonlinear phenomenon of the interaction between light and material, femtosecond laser was adopted to realize many very unique structures and devices which nanosecond laser or picosecond laser is insufficient (Gattass and Mazur, 2008). The microlens structure and MLAs were successfully obtained utilizing femtosecond laser enhanced chemical isotropic etching process (Hao et al, 2012;Chen et al, 2020). The hierarchical micro/nano surface structures were also achieved via femtosecond laser direct writing which inspired numerous researchers to realize surfaces with superwettability (Zhang et al, 2012;Yong et al, 2013Yong et al, , 2020Yin et al, 2017;Duan et al, 2018;Bai et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Benefit from the extreme nonlinear phenomenon of the interaction between light and material, femtosecond laser was adopted to realize many very unique structures and devices which nanosecond laser or picosecond laser is insufficient (Gattass and Mazur, 2008). The microlens structure and MLAs were successfully obtained utilizing femtosecond laser enhanced chemical isotropic etching process (Hao et al, 2012;Chen et al, 2020). The hierarchical micro/nano surface structures were also achieved via femtosecond laser direct writing which inspired numerous researchers to realize surfaces with superwettability (Zhang et al, 2012;Yong et al, 2013Yong et al, , 2020Yin et al, 2017;Duan et al, 2018;Bai et al, 2020;Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al reported a 3D IR ACE consisted of 1200 ommatidia with NA of 0.35. [145] A master mold with concave MLA was first fabricated on a curved BK7 glass substrate by a traditional FLWE method. Then, the 3D nano-imprinting technique was used to transfer the concave structures on a near-IR PMMA plate.…”
Section: Direct Fabrication Methodsmentioning
confidence: 99%
“…f-h) Reproduced with permission. [145] Copyright 2019, Wiley-VCH. www.advmattechnol.de the above work, Liu et al prepared MLA on curved sapphire substrate which was used as a master mold for duplicating convex compound eyes on K9 glass.…”
Section: Direct Fabrication Methodsmentioning
confidence: 99%
“…Micromachines 2021, 12, x 2 of 7 dielectrics [21]. Earlier reports have already proven the effectiveness of the femtosecond laser ablation and etching technologies for fabricating optical devices [22][23][24]. However, the etching process involved in this technology still takes a lot of time.…”
Section: Methodsmentioning
confidence: 99%
“…As an appealing alternative, femtosecond laser manufacturing has become a powerful tool for processing optical devices based on a wide range of materials, including semiconductors [ 19 ], metals [ 20 ], and dielectrics [ 21 ]. Earlier reports have already proven the effectiveness of the femtosecond laser ablation and etching technologies for fabricating optical devices [ 22 , 23 , 24 ]. However, the etching process involved in this technology still takes a lot of time.…”
Section: Introductionmentioning
confidence: 99%